O-05 'It's brilliant! It's working! It's needed!' a hospice short break innovation for young adults. (19th November 2022) - Finlinson, Helen; Spathis, Anna
Abstract : Background: More young adults with life-limiting conditions are surviving into adulthood needing adult palliative care (Gibson-Smith, Jarvis, Norman et al., 2021). The evidence on appropriate service models is sparse (Clark & Fasciano, 2015. Am J Hosp Palliat Med. 31: 101). Adult hospices report lack of competence and confidence in young adult complex care needs (Knighting, Bray, Downing, et al., 2018. J Adv Nurs. May 6). Loss of children's hospice short break provision after transition has been described by families as like 'falling off a cliff edge' (Knighting, Pilkington, Noyes, et al., 2021. Health Serv Deliv Res. 9, 6). There is a lack of equivalent provision in adult services (Together for Short Lives, 2015). To address unmet need, a pilot residential short break service in an adult hospice was co-produced and evaluated with families to determine future provision. Aims: With the aim of facilitating future service optimisation the service evaluation had the following objectives: a) to identify the outcomes and benefits; b) to enable learning; c) to explore staff experiences, training and support needs; d) to scope the financial and service delivery implications. Methods: A service evaluation of the pilot (delivered May 2019-March 2020, ) including process data and feedback gathered using semi-structured questions via questionnaires, interviews and focus groups with young adults, siblings, parent/guardians and staff. Results: Sixty short breaks delivered, accessed by 15 young adults >18 years and their families. Evaluation participants: 3 young adults, 6 siblings, 10 parent/guardians, 11 staff. Highly positive feedback with no withdrawals from the pilot. Triangulated themes: a) social and developmental benefits for young adults; b) respite benefits for families; c) achieving parents' trust, d) ability of adult hospice to meet complex care needs; e) positive staff experiences; f) identified areas for service improvement. Conclusion: Persuasive evidence from the evaluation resulted in the service being commissioned. The report offers recommendations for adult hospices aspiring to develop young adult palliative care services. How innovative or of interest is the abstract?: To our knowledge this is the first young adult short break service in a UK adult hospice.